Рентгеновские комплексы мадис и ультразвуковые комплексы ultima – диагностические средства для оснащения передвижных маммографических кабинетов - Кипенский, Андрей Владимирович; Литвиненко, С. В.; Хоменко, Е. В. (НТУ "ХПИ", 2014)
Использование в передвижных маммографических кабинетах рентгеновских и ультразвуковых диагностических средств, предъявляет к ним дополнительные требования по функциональным возможностям, энергопотреблению, массогабаритным показателям и надежности. В работе, на основе анализа технических данных и режимов работы, показано, что этим требованиям удовлетворяют рентгеновские комплексы МАДИС и ультразвуковые комплексы ULTIMA, которые серийно выпускаются фирмой «РАДМИР» дочерним предприятием АО Научно-исследовательского института радиотехнических измнрений (г. Харьков).

Using X-ray and ultrasound diagnostics in mobile mammography offices makes them more demands on functionality, power consumption, weight and dimensions and reliability. In this paper, based on the analysis of the technical data and operating modes, it is shown that these requirements satisfy the X-ray systems MADIS and ultrasound complexes ULTIMA, which are commercially produced by "RADMIR" DP AO Research Institute of Radio Engineering Measurements (Kharkov). The usefulness of these complexes and devices due primarily to the fact that the results of the survey in the form of images of biological soft tissues of high quality, produced by them, have a high reliability and informative, and allow the identification of a wide range of symptoms in the early stages of breast disease. Good weight and dimension parameters of diagnostic tools and small power can use them not only in stationary, but in the mobile mammography.
X-ray systems Madis and ultrasound complexes ultima - diagnostic tools for equipment mobile mammography cabinets
Keywords: стандарт DICOM; сдвиговолновая эластография; радиотехнческие исследования; mammography; mobile mammography rooms; standard DICOM; shiftwave elastography